2016
DOI: 10.1159/000443312
|View full text |Cite
|
Sign up to set email alerts
|

Second Language Experience Can Hinder the Discrimination of Nonnative Phonological Contrasts

Abstract: Background/Aims: Many studies have shown that experienced second language (L2) learners are more skilled than novice L2 learners at a variety of L2 tasks, including auditory discrimination between members of L2 phonological contrasts. In this paper we argued that while L2 experience is typically beneficial when comparing the effects of more versus less experience, it is not necessarily beneficial when comparing the effects of some experience versus none. Methods: We compared the perceptual assimilation and dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 43 publications
(66 reference statements)
1
14
0
1
Order By: Relevance
“…Findings in studies such as Levy and Strange (2008) converge with the results of many other studies (e.g., Bradlow, Pisoni, Akahane-Yamada and Tohkura, 1997;Wang, Spence, Jongman and Sereno, 1999;Aoyama, Flege, Guion, Akahane-Yamada and Yamada, 2004;Tajima, Kato, Rothwell, Akahane-Yamada and Munhall, 2008) in suggesting that L2 experience generally helps the L2 learner to become more skilled at perceiving the L2 (though see Holliday, 2016 for an interesting counterexample from L1 Mandarin learners of Korean). This positive correlation between L2 experience and L2 perceptual performance can be attributed to two beneficial, and related, outcomes of L2 speech learning: (1) development of mental representations for the contrastive sounds of the L2, particularly those which do not occur in the L1, and (2) development of SPRs for the L2.…”
Section: The Automatic Selective Perception Modelsupporting
confidence: 78%
“…Findings in studies such as Levy and Strange (2008) converge with the results of many other studies (e.g., Bradlow, Pisoni, Akahane-Yamada and Tohkura, 1997;Wang, Spence, Jongman and Sereno, 1999;Aoyama, Flege, Guion, Akahane-Yamada and Yamada, 2004;Tajima, Kato, Rothwell, Akahane-Yamada and Munhall, 2008) in suggesting that L2 experience generally helps the L2 learner to become more skilled at perceiving the L2 (though see Holliday, 2016 for an interesting counterexample from L1 Mandarin learners of Korean). This positive correlation between L2 experience and L2 perceptual performance can be attributed to two beneficial, and related, outcomes of L2 speech learning: (1) development of mental representations for the contrastive sounds of the L2, particularly those which do not occur in the L1, and (2) development of SPRs for the L2.…”
Section: The Automatic Selective Perception Modelsupporting
confidence: 78%
“…Many researchers have explored the perceived similarity between L1 and L2 sounds by L2 learners (e.g., Escudero & Williams, 2011;Holliday, 2016;Strange, Akahane-Yamada, Fitzgerald, & Kubo, 1996). Their findings showed that L2 learners assimilated the non-native sounds to their closest L1 categories.…”
Section: Introductionmentioning
confidence: 99%
“…One finding showed the effects of L2 experience in that PF /y/ was significantly assimilated to / j u/ by ModExp group as opposed to by NoExp group and by HiExp group suggesting that learners have different degrees of perceived similarity depending on their L2 experience background. Another example is from the study of Holliday (2016) investigating the perception, identification and discrimination of Korean sibilants /s h / and /s*/ (tense version of Korean /s/) by three groups of native Mandarin speakers: naïve listeners (NM), novice L2 learners (novice MK), advanced L2 learners (advanced MK). These fricatives were followed by one of these vowels: /a, i, u/.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In one such recent study of the perception of the Korean sibilant fricative contrast /s h /-/s*/ by L1 speakers of Mandarin Chinese (hereafter, Mandarin), Holliday (2016) showed that L2 learners generally assimilated the initial consonant in both Korean /s h a/ and /s*a/ to Mandarin /s/. Naïve listeners, on the other hand, were more likely than L2 learners to perceptually assimilate Korean /s h a/ (but not /s*a/) to a Mandarin affricate category, such as /ʦ ʰ / or /ʧ ʰ /, a result that was also found in Holliday (2014b).…”
Section: Introductionmentioning
confidence: 99%